2015
DOI: 10.17221/696/2014-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic amides (avenanthramides) in oats - a review

Abstract: Boz H. (2015): Phenolic amides (avenanthramides) in oats -a review. Czech J. Food Sci., 33: 399-404.Whole grain cereals such as oats are important sources of phenolic compounds. Oats contain phenolic amides, also named avenanthramides (AVAs), which have beneficial health properties because of their antioxidant, anti-inflammatory, and antiproliferative effects. The most common avenanthramides are esters of 5-hydroxyanthranilic acid with p-coumaric (AVA-A), ferulic (AVA-B), or caffeic (AVA-C) acids. The studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…In this regard, a more than four-fold increase in TPC was obtained after five days of germination in darkness at 25 • C/60% RH. Similar results have been previously reported [17,45,52]. This result could also reflect the better extractability of phenolic compounds from kernel structures after germination [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, a more than four-fold increase in TPC was obtained after five days of germination in darkness at 25 • C/60% RH. Similar results have been previously reported [17,45,52]. This result could also reflect the better extractability of phenolic compounds from kernel structures after germination [17].…”
Section: Discussionsupporting
confidence: 91%
“…Studies regarding the chemopreventive effect of oat sprouts and whole oats are limited in comparison with those discussing the unique polyphenolic alkaloids-AVAs-exclusively extracted from oats, among other compounds such as steroidal saponins, β-glucan, and flavonoids [5,[9][10][11]13,15,44,45,52,[65][66][67][68], mainly through mechanisms related to their antioxidant, anti-inflammatory, immunomodulatory, antiproliferative, proapoptotic, cancer cell growth, and senescence control activities. These studies suggest that the notion of effective antitumor activity arising from whole oats may be due to the synergistic effects of multiple compounds rather than any one nutrient or compound alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Xu et al (2009) was reported that gallic acid, vanillic acid, caffeic acid, ferulic acid, and p-coumaric acid are the main PAs in oats. The content of FA in oat bran was 33 mg/100g (Boz 2015). In the study by Chen et al (2018) was reported that FA was in range 1.32 -l8.98 μg/g.…”
Section: Validation Of Methodsmentioning
confidence: 88%
“…AVNs are a group of unique soluble bioactive compounds that are absent in other food crops. Oats contain a unique group of approximately 40 different types of AVNs that consist of an anthranilic acid derivatives and hydroxycinnamic acid derivatives (Boz 2015). AVNs from oats exhibit (potent) antioxidant activity in vitro and in vivo (Thomas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They act as strong free radical scavengers and have showed lowering cholesterol abilities (Peterson & Qureshi, 1993). As in the case of OBG, despite the fact that AVAs have exhibited bioavailability ,antioxidant (Chen et al, 2007), and anti-inflammatory (Koenig et al, 2014) properties in humans, they also demonstrated poor stability during steaming, autoclaving, and flaking (Boz, 2015). Consequently processing steps need to be taken into account in order to establish effective relationship regarding their health promoting benefits.…”
Section: Oats Constituents and Biological Activitiesmentioning
confidence: 99%